Domestic Poultry and SARS Coronavirus, Southern China - David E. Swayne; David L. Suarez; Erica Spackman; Terrence M. Tumpey; Joan R. Beck; Dean D. Erdman; Pierre E. Rollin; Thomas G. Ksiazek (Emerging Infectious Diseases, 2004)
SARS coronavirus injected intratracheally into chickens, turkeys, geese, ducks, and quail, or into the allantoic sac of their embryonating eggs, failed to cause disease or replicate. This finding suggests that domestic poultry were unlikely to have been the reservoir, or associated with dissemination, of SARS coronavirus in the animal markets of southern China.